Aerial view of Port of Spain, its harbour and shadowing hills - Norton, Noel P. (Trinidad Photographers Ltd., 2010)
Photo showing an aerial view of the harbour and shadowing hills of Port of Spain, Trinidad. The card also bears a handwritten correspondence. No. 004.
Colour: Red, Blue, Brown and Green Hues ; Style: Landscape ; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trinidad and Tobago--Aerial Views; Harbors--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain